Non-Kolmogorov atmospheric turbulence and orbital angular momentum of entangled states for optical communication - Yuejin Yang; Donghui Yang; Jicheng Wang; Yun Zhu; Zhengda Hu; Yixin Zhang (Results in Physics, 2019)
We extend the theory of detection probabilities of single-photon communication in turbulent atmosphere to the entangled case and derive analytical expressions for detection probabilities. We show that the rotational field correlation in the entangled case cannot be expressed as a straightforward extension from the disentangled case. By considering the orbital angular momentum (OAM) entangled Laguerre-Gaussian (LG) beams for illustration, we explore the effect of non-Kolmogorov atmospheric turbulence on the probabilities of both the biphoton detection and the single-photon detection. The entanglement of OAM LG beams contributes positively to the faithful detection probability. The change of maximal crosstalk probability in the detection process is also explored, which displays the non-linear dependence on the crosstalk quantum number. Keywords: Atmospheric turbulence, Orbital angular momentum, Entanglement, Optical communication